ADOMIAN-PADE APPROXIMATE SOLUTIONS TO THE CONFORMABLE NON-LINEAR HEAT TRANSFER EQUATION - Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru (Vinca Inst Nuclear Sci, 2019)
This paper adopts the Adomian decomposition method and the Pade approximation technique to derive the approximate solutions of a conformable heat transfer equation by considering the new definition of the Adomian polynomials. The Pade approximate solutions are derived along with interesting figures showing the approximate solutions.
Keywords: Adomian decomposition method; conformable heat transfer equation; Pade approximation